2006
DOI: 10.1038/ng1771
|View full text |Cite|
|
Sign up to set email alerts
|

BBS10 encodes a vertebrate-specific chaperonin-like protein and is a major BBS locus

Abstract: Bardet-Biedl syndrome (BBS) is a genetically heterogeneous ciliopathy. Although nine BBS genes have been cloned, they explain only 40-50% of the total mutational load. Here we report a major new BBS locus, BBS10, that encodes a previously unknown, rapidly evolving vertebrate-specific chaperonin-like protein. We found BBS10 to be mutated in about 20% of an unselected cohort of families of various ethnic origins, including some families with mutations in other BBS genes, consistent with oligogenic inheritance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
240
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(264 citation statements)
references
References 15 publications
11
240
1
9
Order By: Relevance
“…In order to map novel BBS genes we undertook genetic linkage studies in a large Omani BBS kindred. We mapped a novel locus to chromosome 12q21.2 that overlapped the recently described BBS10 locus 21 and, furthermore, confirmed mutations in the BBS10 gene, FLJ23560. We also excluded linkage to the recently described BBS11 locus on chromosome 9q33.…”
Section: Introductionmentioning
confidence: 72%
“…In order to map novel BBS genes we undertook genetic linkage studies in a large Omani BBS kindred. We mapped a novel locus to chromosome 12q21.2 that overlapped the recently described BBS10 locus 21 and, furthermore, confirmed mutations in the BBS10 gene, FLJ23560. We also excluded linkage to the recently described BBS11 locus on chromosome 9q33.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, rhodopsin is a candidate protein that would be transported with assistance of BBS proteins, including MKKS, although other target proteins also must exist. In addition to MKKS , BBS10 (Stoetzel et al, 2006), and BBS12 (Stoetzel et al, 2007) are now known to share weak but significant sequence similarity to the group II chaperonins, including CCT. These proteins might assist protein transport by performing chaperone-like activities, although the exact molecular mechanisms of MKKS-dependent transport remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequence similarity between MKKS protein and group II chaperonins suggests that MKKS function may have evolved from the chaperonin family . In addition to MKKS, two other BBS proteins, BBS10 (Stoetzel et al, 2006) and BBS12 (Stoetzel et al, 2007), were recently shown to share weak but significant sequence similarities with group II chaperonins. Interestingly, none of the three chapeonin-like BBS proteins were found in the BBSome (Nachury et al, 2007), suggesting that these chaperonin like proteins have a distinctive role in BBS-associated functions.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder is characterized by retinitis pigmentosa, renal malformations, situs inversus, cardiomyopathy, diabetes and polydactyly. Mutations in a number of genes are known to cause BBS, and there is evidence that all BBS proteins participate in a common cellular process, given that mutations in any BBS gene result in clinically related phenotypes (Katsanis, 2004;Nishimura et al, 2005;Stoetzel et al, 2006). BBS proteins are located at the basal body of cilia and centrosomes (during cell cycle), and it is proposed that these proteins assist microtubule-related transport and cellular organization processes relating to ciliary and centrosomal activities (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%